Is intracrinology of endometriosis relevant in clinical practice? A systematic review on estrogen metabolism - Mercorio, Antonio; Giampaolino, Pierluigi; Romano, Andrea; Dällenbach, Patrick; Pluchino, Nicola (Frontiers in Endocrinology, 2022)
Endometriosis is a chronic, multifactorial, estrogen-dependent disease. The abnormal endocrine microenvironment of endometriosis lesions is considered a main feature and multiple enzymatic pathways leading to local increased synthesis of estrogens have been identified. However, the relevance of intracrinology in clinical practice is still lacking. Medline, Embase, Scopus database were systematically searched for studies reporting on local estrogens metabolism of endometriotic lesions. The main enzymatic pathways involved in the intracrinology of endometriosis such as aromatase (CYP19A1), 17β-hydroxysteroid dehydrogenase (HSD17B) type 1, type 2 and type 5, steroid sulfatase (STS), estrogen sulfotransferase (SULT1E1) were assessed with a critical perspective on their role in disease endocrine phenotyping, drug resistance and as therapeutic targets. Overall, studies heterogeneity and missing clinical data affect the interpretation of the clinical role of these enzymes. Although the use of some drugs such as aromatase inhibitors has been proposed in clinical practice for two decades, their potential clinical value is still under investigation as well as their modality of administration. A closer look at new, more realistic drug targets is provided and discussed. Altered expression of these key enzymes in the lesions have far reaching implication in the development of new drugs aimed at decreasing local estrogenic activity with a minimal effect on gonadal activity; however, given the complexity of the evaluation of the expression of the enzymes, multiple aspects still remains to be clarified.